LIMITATIONS OF CLINICAL AUTHORITY AND MEDICAL PRACTICE THROUGH APPLICATION-BASED TELEMEDICINE - Chandrika Karisa Adhalia (Indonesia Private Law Review, 2023)
Telemedicine is a technology-based health service that can be carried out remotely by health workers to improve public health. This study aims to determine the status of telemedicine service provider applications in medical practice therapeutic transactions, the status of doctors' practice licenses (SIP) in telemedicine practice, and the limits of clinical authority that doctors can exercise in providing medical services form of Telemedicine. This research method is normative juridical by analyzing library materials, secondary legal materials, and the results of interviews with informants. The study results found that the telemedicine service provider application is not an official health facility, the SIP used as a requirement in telemedicine-based applications does not comply with applicable regulations, and the limited clinical authority for telemedicine practice is consultation and initial therapy.